2014
DOI: 10.1080/07399332.2013.862799
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating Respectability: Migrant Women Workers’ Perceptions of Relationships and Sexuality in Free Trade Zones in Sri Lanka

Abstract: Migration has implications for women's sexual and reproductive health and rights. Our purpose with this study was to explore unmarried migrant women's perceptions of relationships and sexuality in the context of Sri Lankan Free Trade Zones. Sixteen semi-structured qualitative interviews were analyzed using thematic analysis. We found that the women's perceptions were influenced by gendered hegemonic notions of respectability and virginity. Complex gender relations both worked in favor of and against women's se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…They are easily infected and transmit the disease to the spouse and others [4]. Female domestic migrant workers are at risks of STD, unwanted pregnancy, illegal termination of pregnancy and related problems [5] Female migration workers play an important role in HIV spread [6] Irregular migrant workers do not have access to HIV/AIDS awareness campaigns on the electronic, print and other mass media. Even the message provided by television/radio advertisements did not make an impact as, in the popular perception.…”
Section: Discussionmentioning
confidence: 99%
“…They are easily infected and transmit the disease to the spouse and others [4]. Female domestic migrant workers are at risks of STD, unwanted pregnancy, illegal termination of pregnancy and related problems [5] Female migration workers play an important role in HIV spread [6] Irregular migrant workers do not have access to HIV/AIDS awareness campaigns on the electronic, print and other mass media. Even the message provided by television/radio advertisements did not make an impact as, in the popular perception.…”
Section: Discussionmentioning
confidence: 99%
“…Three of the female participants admitted that they engaged in transactional sex. Many recent studies have demonstrated that women's motivations for engaging in transactional sex are aligned to globalisation, in that the proceeds from transactional sexual encounters are used to purchase the symbols of global beauty propagated by the local and global print and visual media (Camlin et al 2010, Greif & Dodoo 2011; Hirsch 2014; Hunter 2010; Jordal, Wijewardena, Öhman, Essen & Olsson 2014; Roy et al 2010; Stoebenau, Stephanie, Rubincam, Willan, Zembe, Tsikoane, et al 2011; Weine & Kashuba 2012; Zembe, Townsend, Thorson & Ekstrom 2013). These women have come to be known as ‘global citizens in local states’ (Robins 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The authors were acquainted with the area from previous work done with migrant women workers in the FTZ [21]. Purposive sampling was chosen to achieve a variety of perceptions.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, contextualized knowledge of men’s understandings of masculinities and femininities is imperative for the development of theory, policies and interventions towards improved SRHR of women and men. While previous studies of Sri Lankan FTZ have investigated migrant women workers’ relationships, sexuality and SRHR risks [10,14,21], to our knowledge, there has been no investigation of men’s perceptions of these issues in this context.…”
Section: Introductionmentioning
confidence: 99%